Effect of foliar application of IAA And GA on sex expression, yield attributes and yield of bitter gourd (Momordica Charantia L.) - Akter, Pervin; Rahman, MA (Chittagong University Journal of Biological Sciences, 2013)
Three concentrations of each of IAA viz. 2.5 (T1), 5.0 (T2) and 10 (T3) ppm and GA3 viz. 2.5 (T4), 5.0 (T5) and 10 (T6) ppm were applied as foliar spray on bitter gourd. Results showed a positive stimulatory effect in the increase of female flowers at T3 where the male to female sex ratio was the lowest. The number of fruits, fresh weight of fruits and yield per plant were also found to be the highest at T3. DOI: http://dx.doi.org/10.3329/cujbs.v5i1.13370 The Chittagong Univ. J. B. Sci.,Vol. 5(1 &2):55-62, 2010